Perkembangan Hukum Keluarga Islam Di Negara Uni Emirat Arab - Mardiah (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Islamic family law reform has been carried out by many Muslim countries. The purpose of the reform is to produce legal products that are in accordance with the needs of modern society in the country. One of the countries that renewed Islamic family law is the United Arab Emirates. The United Arab Emirates renewed the Islamic Family Law by reinterpreting the texts of the Qur'an and Hadith and based on the principles of family law in the Maliki school. This research aims to find out how the dynamics of Islamic family law reform in the United Arab Emirates. This research is a type of library research. The data is collected using documentation techniques, namely the collection of written data in the form of scientific articles of research results and books related to the research. The results of this study found that the United Arab Emirates first codified family law in 1985. Then in 2005 reformed its family law by issuing Federal Law Number 28 of 2005 concerning Personal Legal Status. In reforming family law, the United Arab Emirates used the method of talfiq and ijtihad. The elements of reform in Federal Law No. 28/2005 on Personal Legal Status include: marriage, marriage contract and registration, age of marriageability and kafa'ah, relationship between husband and wife, divorce, and khuluk.